2002
DOI: 10.1159/000064935
|View full text |Cite
|
Sign up to set email alerts
|

Leptin Modulates the Inflammatory Response in Acute Pancreatitis

Abstract: Background: Leptin is a pleiotropic hormone that is involved in the regulation of food intake and body weight. Recent findings demonstrated that leptin receptors are present in the pancreas but the involvement of leptin in pancreatitis remains unknown. The aim of the present study was: (1) to assess plasma leptin levels in rats with caerulein-induced pancreatitis (CIP) and humans with acute pancreatitis; and (2) to determine the effects of exogenous leptin on the course of acute CIP in rats Methods: CIP was pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
42
1
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 27 publications
3
42
1
1
Order By: Relevance
“…In a recent study, Konturek et al (2002) have shown that acute pancreatitis in rats and in humans is associated with a marked increase in the plasma level of leptin. The authors claimed that inflamed pancreas could be the source of local production of leptin.…”
Section: Discussionmentioning
confidence: 98%
“…In a recent study, Konturek et al (2002) have shown that acute pancreatitis in rats and in humans is associated with a marked increase in the plasma level of leptin. The authors claimed that inflamed pancreas could be the source of local production of leptin.…”
Section: Discussionmentioning
confidence: 98%
“…In caerulein-induced pancreatitis (CIP), plasma leptin levels are increased and the onset of pancreatitis is accompanied by increased pancreatic expression of the leptin gene [14]. In CIP rats, leptin decreases the plasma level of TNFα and increases the plasma level of IL-4, an anti-inflammatory cytokine [12].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, failure to express these anti-inflammatory proteins may contribute to severity of the response in obesity. Because leptin regulates inflammation and exerts acute protective effects in models of AP (13)(14)(15), it was important to differentiate between the direct effects of leptin deficiency and those mediated by massive obesity. Short-term leptin administration did not protect ob/ob mice from AP and actually worsened hypocalcaemia and resulted in increases in lipase, SAA, and IFN-␥ levels.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with AP, a correlation between serum leptin and disease severity has been reported by some investigators but not by others (11,12). Although in animal models administration of leptin decreases AP severity (13)(14)(15)(16), more severe disease is present in leptin-deficient ob/ob and leptin receptordeficient db/db mice as well as leptin-receptor mutant fa/fa rats (17,18). However, the differential effect of obesity versus leptin deficiency has not been fully investigated.…”
mentioning
confidence: 99%